Implication of bioethics in enterprise B and BIC - Siesquen-More, Jorge Arturo (2024)
It is inevitable to realize that the enterprise has faced social, moral, political and economic movements, giving rise to new figures of business, revolutionizing the economic market. B and BIC companies change the traditional way of conceiving the enterprise as that instrument only capable of receiving and maximizing income, for another that, maintaining this function, has the intention of contributing positively to the problems that afflict the community in general, promoting an impact in the social, economic and environmental sphere. The present work analyzes how companies B and BIC can be seen from a bioethical aspect, based on the bibliographic review in academic repositories, identifying that companies B and BIC by seeking to be the prototype of a enterprise with corporate social responsibility par excellence, provide importance to both the entrepreneurial subject and all other subjects involved in the development of their activities; which has made it possible to determine that the companies in question have a personalist bioethical approach. Likewise, when facing these issues, certain ethical-moral controversies must resort to the essential principles of bioethics, also noting the implication of principlist bioethics with companies B and BIC. Finally, it is recognized that both enterprise B and BIC are closely linked to the origin of the nascent concept of business bioethics.